(untitled) (Tanzania Medical Journal, 2025)
Background International ethical guidelines for biomedical research involving human subjects recognize the importance of obtaining permission from community leaders before conducting research in low-resource countries. The guidelines emphasize that community permission does not replace the requirement for individual informed consent. However, there is limited understanding of the role of community leaders’ play in this process. This study aimed to explore the experiences of community leaders’ involvement in the informed consent process during malaria clinical trial conducted in Tanzania. Methods This exploratory case study was conducted in three purposively selected villages in Tanga region. In-depth interviews were conducted with community leaders using a semi-structured interview guide and all interviews were audio-recorded using a digital recorder. Data were organized using NVivo software, and thematic analysis was applied. Results The study identified key themes in involving community leaders during obtaining consent. A clear demarcation of responsibilities between community leaders and researchers is necessary to minimize the potential influence of leaders’ authority over community. shared information raised concerns about maintaining participants confidentiality. Conclusion and Recommendation The findings suggest that study information and clear demarcation of responsibilities between community leaders and researchers should be communicated clearly from beginning to end. This promotes trust, supports voluntary participation, ensures confidentiality, and provides a clear understanding of the risks and benefits involved.